2011
DOI: 10.1088/0004-637x/742/1/26
|View full text |Cite
|
Sign up to set email alerts
|

A CROSSED MOLECULAR BEAM, LOW-TEMPERATURE KINETICS, AND THEORETICAL INVESTIGATION OF THE REACTION OF THE CYANO RADICAL (CN) WITH 1,3-BUTADIENE (C4H6). A ROUTE TO COMPLEX NITROGEN-BEARING MOLECULES IN LOW-TEMPERATURE EXTRATERRESTRIAL ENVIRONMENTS

Abstract: We present a joint crossed molecular beam and kinetics investigation combined with electronic structure and statistical calculations on the reaction of the ground-state cyano radical, CN(X 2 Σ +), with the 1,3-butadiene molecule, H 2 CCHCHCH 2 (X 1 A g), and its partially deuterated counterparts, H 2 CCDCDCH 2 (X 1 A g) and D 2 CCHCHCD 2 (X 1 A g). The crossed beam studies indicate that the reaction proceeds via a long-lived C 5 H 6 N complex, yielding C 5 H 5 N isomer(s) plus atomic hydrogen under single coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 43 publications
4
67
0
Order By: Relevance
“…The reaction of the cyano radical (CN), which is isoelectronic with C 2 H, with 1,3-butadiene has also been studied [27]. Previous studies of the reactions of the isoelectronic C 2 H and CN radicals with unsaturated hydrocarbons have shown that they react similarly, both in terms of reaction rate and major products [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of the cyano radical (CN), which is isoelectronic with C 2 H, with 1,3-butadiene has also been studied [27]. Previous studies of the reactions of the isoelectronic C 2 H and CN radicals with unsaturated hydrocarbons have shown that they react similarly, both in terms of reaction rate and major products [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…CN + 1,3-butadiene proceeds via addition and H-elimination to yield isomers of C 5 H 5 N. Crossed-molecular beams experiments suggest a maximum of 3-6% pyridine and 94-97% 1-cyano-1,3-butadiene is formed under single collision conditions. Rice-Ramsperger-Kassel-Marcus (RRKM) calculations predict only 0.02% pyridine formation at 0 eV collision energy, with a maximum of 6% at the limits of the errors of the calculations [27]. If C 2 H + 1,3-butadiene were analogous to CN + 1,3-butadiene, one might expect a small branching fraction for benzene, with the remainder of the products being 1,3-hexadien-5-yne.…”
Section: Introductionmentioning
confidence: 99%
“…For all these reasons, CN reactions with small unsaturated hydrocarbons have been widely investigated in kinetics [1,[16][17][18][19][20][21][22][23] and reaction dynamics [24][25][26][27][28][29][30][31][32] experiments. More specifically, the reaction CN + C 2 H 4 was found to be very fast, approaching the gas kinetics limit, at very low and high temperatures [16,23], confirming its role in cold and hot environments.…”
Section: Introductionmentioning
confidence: 99%
“…Present experimental work has shown that reactions with carbon containing radicals usually lead to products that are carbon enriched with respect to the reagent [18] and then these processes can be important routes to the construction of ring species many of which are of biological importance. For instance, a very recent work concerning the reaction of the cyanide radical CN with the 1,3-butadiene molecule, H 2 CCHCHCH 2 , provided some evidence that the aromatic pyridine C 5 H 5 N could be produced although in small quantity [113]. Therefore reactions of simple stable C 2 , C 3 and C 4 -based hydrocarbons with radicals should also be completed.…”
Section: Neutralsmentioning
confidence: 99%